1997
DOI: 10.1177/0164027597194004
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Depression Measure among American Indian Elders: Confirmatory Factor Analysis of the CES-D Scale

Abstract: This research examines differences in depressive symptomology among urban, rural off-reservation, and reservation-residing American Indians, age 55 years or older, of the eastern Great Lakes region. It analyzes the measurement structure of one commonly used depression scale, the Center for Epidemiological Studies Depression Scale, and tests alternative models for the full sample (N = 277) as well as the three residential strata. Findings show that a 12-item version developed by Liang et al. for use with Mexica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
6
37
0
1
Order By: Relevance
“…For example, culture and ACE are inextricably interwoven together; the reporting accuracy of ACE may vary due to individuals' background (e.g., age, gender, race) or culture (Easton, 2012). Also, some depression scales, such as the Center for Epidemiological Studies Depression Scale, have been found to be conceptually valid in an AI population in the great region (Chapleski, Lamphere, Kaczynski, Lichtenberg, & Dwyer, 1997). However, the validity of the GDS has not yet been evaluated with AI/ AN populations.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, culture and ACE are inextricably interwoven together; the reporting accuracy of ACE may vary due to individuals' background (e.g., age, gender, race) or culture (Easton, 2012). Also, some depression scales, such as the Center for Epidemiological Studies Depression Scale, have been found to be conceptually valid in an AI population in the great region (Chapleski, Lamphere, Kaczynski, Lichtenberg, & Dwyer, 1997). However, the validity of the GDS has not yet been evaluated with AI/ AN populations.…”
Section: Limitationsmentioning
confidence: 99%
“…The CES-D (Radloff, 1977) is one of the most widely used measures of depressive symptoms and has been included in a number of studies with Indigenous samples (e.g., Beals, Manson, Keane, & Dick, 1991; Chapleski, Lamphere, Kaczynski, Lichtenberg, & Dwyer, 1997; Dick, Beals, Keane, & Manson, 1994; Manson, Ackerson, Dick, Baron, & Fleming, 1990). The CES-D was developed to assess symptoms associated with major depression, specifically, “depressed mood, feelings of guilt and worthlessness, feelings of helplessness and hopelessness, psychomotor retardation, loss of appetite and sleep disturbances” (Radloff, 1977, p. 386).…”
Section: The Center For Epidemiologic Studies Depression Scalementioning
confidence: 99%
“…Shore and Manson (1981) warn that it is a serious error to generalize from the EuroAmerican Westernized view of depression to Indian experiences and behavior. Although there have been many studies employing the CES-D in different groups (Liang, Van Tran, Krause, & Markides, 1989;McCallum, Mackinnon, Simons, & Simons, 1995), only a few studies have addressed Chapleski et al / American Indian Elders 43 older American Indians (Baron, Manson, Ackerson, & Brenneman, 1989;Chapleski, Lamphere, Kaczynski, Lichtenberg, & Dwyer, 1997;Somervell, Beals, Kinzie, Boehnlein, Leung, & Manson, 1993a, 1993b.…”
Section: American Indian Mental Healthmentioning
confidence: 99%
“…A 12-item model found to be valid for American Indian elders (Chapleski, Lamphere, et al, 1997) is used as the dependent measure. The 12-item scale was previously found to have three positive attributes that favor its use over the original 20-item scale-parsimony, better overall goodness of fit to the data, and conceptual appropriateness.…”
Section: Dependent Measure-ces-dmentioning
confidence: 99%